Book Review:Reimagining the Creative Industries: Youth Creative Work, Communities of Care (Miranda Campbell: Routledge, 2022) - McKeever, Louise (Irish Journal of Arts Management and Cultural Policy, 2023)
In Reimagining the Creative Industries: Youth Creative Work, Communities of Care, Dr Miranda Campbell presents a fresh and engaging vision for the future of the creative industries through community youth arts programs and their role in fostering inclusivity, collaboration, and social change. Campbell challenges conventional notions of the creative industries, highlighting the transformative potential of youth creative work within communities of care. The book explores topics such as care ethics, diversity and inclusion, inclusive spaces for small-scale cultural production, and collaborative production in communities of practice. With well-supported arguments and practical insights, Campbell's work contributes significantly to the field of arts management and cultural policy.